Money, power, and war in the medieval Mediterranean. The consequences of the sinking of a Catalan merchant ship near Siracuse in 1429 (Edad Media. Revista de Historia, 2025)
In 1429 a Catalan merchant ship was sunk off the waters of Syracuse by a famous Genoese skipper, Paolo Cicogna, who was often considered as a pirate. In this paper we analyse the consequences of this attack, which took place in a context of intense political tensions between the main powers of the western Mediterranean (Crown of Aragon, Genoa, Milan and Florence). This situation influenced the management of the commercial conflict initiated by the merchants affected, including Joan de Torralba from Barcelona, whose socio-political capital facilitated the granting of a letter of mark or reprisal by Alfonso the Magnanimous against the republic of Florence.
Keywords: Commerce; Retaliations; Crown of Aragon; Genoa; Florence